Efektivitas Benda Konkret Dalam Pembelajaran Kooperatif Operasi Bilangan Cacah Besar Sekolah Dasar Kelas IV - Wardhani, Nurina Artistiana; Marliana Susianti, Oni (JISPE Journal of Islamic Primary Education, 2025)
The low level of student interest and participation in science and social science learning in elementary schools, particularly in the topic of Light and Its Properties, poses a challenge that affects the effectiveness of the learning process. This study aims to determine the effect of applying the Make a Match method in increasing students' interest and participation in learning. The research employed a qualitative approach with a case study method focused on a single fifth-grade student from class V-B at SDN Gobang 01, who initially showed very low learning engagement. Data were collected through observations and interviews during two phases of learning, before and after the implementation of the Make a Match method. The results showed that after applying the Make a Match method, there was a significant increase in both learning interest and participation. The student’s participation improved to 64%, as reflected in their increased willingness to ask questions, answer, and actively engage in classroom discussions. The student also demonstrated greater enthusiasm toward the subject matter. It can be concluded that the Make a Match method is effective in enhancing learning interest and participation among previously passive students, particularly in science subjects at the elementary level. This study recommends that teachers adopt more interactive and participatory teaching strategies to create enjoyable learning environments and foster comprehensive student engagement.